The interaction between visual resolution and task-relevance in guiding visual selective attention - Peterson, Jared Joel (Kansas State University, 2018)
Visual resolution (i.e., blur or clarity) is a natural aspect of vision. It has been used by film makers to direct their audience’s attention by focusing the depth of field such that the critical region in a scene is uniquely clear and the surrounding is blurred. Resolution contrast can focus attention towards unique clarity, as supported by previous eye tracking and visual search research (Enns & MacDonald, 2013; Kosara, Miksch, Hauser, Schrammel, Giller, & Tscheligi, 2002; & McConkie, 2002; Peterson, 2016; Smith & Tadmor, 2012). However, little is known about how unique blur is involved in guiding attention (e.g., capture, repel, or be ignored). Peterson (2016) provided reaction time (RT) evidence that blur is ignored by selective attention when resolution is not task-relevant. Perhaps visual resolution is a search asymmetry where unique clarity can be used to guide selective attention during search, but unique blur cannot guide attention. Yet, perhaps the RT evidence was not sensitive enough with Peterson’s (2016) methodology to observe unique blur capturing or repelling attention. Eye movements (e.g., letter first fixated) may be more sensitive than RT as it measures blur and clarity’s influence on guiding attention earlier in a trial. The current study conducted three experiments that investigated: a) how visual resolution guides attention when it is task-irrelevant (Exp. 1), b) whether visual resolution is a search asymmetry, by manipulating resolution’s task-relevance (Use Blur, Use Clarity, Do Not Use Unique Blur or Clarity, & No Instructions) (Exp. 2), and c) whether blur and/or clarity are processed preattentively or require attention (Exp. 3). Experiments 1 and 2 manipulated blur and clarity (Exp. 1 Resolution = Task-irrelevant & Exp. 2 Resolution = Task-relevant), during a rotated L and T visual search measuring RT and eye movements. Experiment 1 found with the more sensitive eye movement measures that unique clarity strongly captured attention while unique blur weakly repelled attention towards nearby clarity (or clarity, especially that close to blur, captured attention). Experiment 2 found evidence that visual resolution is not a search asymmetry because the influence of resolution on selective attention was contingent upon its task-relevance, which theoretically supports the presence of a reconfigurable resolution feature detector. Experiment 3 used a feature search for either blur or clarity (i.e., resolution was task-relevant) and compared RT x Set Size search slopes. Both blurred and clear target present RT x Set Size search slopes were ~ 1 msec/item. The results strongly supported that blur and clarity are both processed preattentively, and provided additional evidence that resolution is not a search asymmetry. Overall, the current studies shed light on how visual resolution is processed and guides selective attention. The results revealed that visual resolution is processed preattentively and has a dynamic relationship with selective attention. Predicting how resolution will guide attention requires knowledge of whether resolution is task relevant or irrelevant. By increasing our understanding of how resolution contrast guides attention, we can potentially apply this knowledge to direct viewers’ attention more efficient using computer screens and heads-up displays.
Keywords: Visual resolution; Visual selective attention; Visual Blur; Visual Search; Task-relevance; Eye movements